2001
DOI: 10.1038/sj.ejcn.1601228
|View full text |Cite
|
Sign up to set email alerts
|

Folate fortification: potential impact on folate intake in an older population

Abstract: Objective: To examine the potential impact of different models of folate fortification of Australian foods on the folate intakes of older Australians. Design: Dietary data were collected using a food frequency questionnaire from people attending a populationbased health study. Setting: Two postcode areas west of Sydney, Australia. Subjects: A total of 2895 people aged over 49 y, obtained from a door knock census (79% of 3654 subjects examined). Main outcome measures: The folate intake in this population was es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Folate intake also increased substantially and significantly over the 10-year period largely due to an increase in folate from fortified foods, mainly in breakfast cereals and yeast extracts, which commenced in Australia in 1997 (around the start of the second data collection period) (Abraham and Food consumption trends in older Australians VM Flood et al Flood et al, 2001). Some authors (Hickling et al, 2005) had predicted that voluntary folate fortification may not be able to achieve any significant changes to folate intake, but these data provide evidence that significant changes have been achieved with voluntary fortification, in at least this subpopulation.…”
Section: Discussionmentioning
confidence: 99%
“…Folate intake also increased substantially and significantly over the 10-year period largely due to an increase in folate from fortified foods, mainly in breakfast cereals and yeast extracts, which commenced in Australia in 1997 (around the start of the second data collection period) (Abraham and Food consumption trends in older Australians VM Flood et al Flood et al, 2001). Some authors (Hickling et al, 2005) had predicted that voluntary folate fortification may not be able to achieve any significant changes to folate intake, but these data provide evidence that significant changes have been achieved with voluntary fortification, in at least this subpopulation.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have suggested that vitamin B12 should be added to any folate-fortified foods. 22,23 Because our earlier research showed that most older people who would be likely to consume high levels of folate are those who take supplements containing folic acid, 8 it is recommended that vitamin B12 be included in any vitamin supplements containing folate.…”
Section: Discussionmentioning
confidence: 99%
“…3 In Australia, folate fortification of food is voluntary, and breakfast cereals are the main products fortified. In previous research, 8 we examined the potential impact on folate intake in older people if folate fortification became mandatory in Australia. Under this scenario, our results showed that only 0.5% of the study population would be likely to consume levels greater than 1000 µg per day from synthetic folic acid, the intake considered by the Institute of Medicine (IOM) as the tolerable upper intake level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A strong discourse was introduced into the news reporting from August 2004 and continues into the second last month of analysis, just before the mandatory decision is announced. This discourse raises serious concerns about the risks of fortification of bread with headlines such as Cereals raise concern (The Christchurch Press, 18 The occasional journal article in the time period acknowledged potential iatrogenic risks of fortification [29][30][31] but also referred to range of wider risks, such as Australia's lack of national nutrition monitoring and surveillance system to use as basis for policy decisions. 32 These other concerns are not as clearly articulated in media representation.…”
Section: Fortification As Iatrogenicmentioning
confidence: 99%